Perbedaan Tingkat Perkembangan Anak Usia 3-4 Tahun yang Tidak Mengikuti Aktifitas Bermain dan yang Mengikuti Aktifitas Bermain PAUD di Desa Jatinom Kecamatan Kanigoro Kabupaten Blitar - Rizkianna Nur Wirian; Ika Agustina (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2015)
Midwifery care is pregnancy health education courses in midwifery in order to get the optimal result required an innovative learning models. There are many models of learning one is Problem based learning.Thus researchers want to analyze the effectiveness of Problem Based Learning in Pregnancy on Obstetrical Care learning Diploma Program. This research were done in STIKes Patria Husada Blitar, On 25 February until march 8 th 2014.Methode: The research use kuantitatif approach, True experimental. Population and sampel is student in college third semesters. Amount of 38 student,divide into 2 groups, choice in random. Independent Variable Problem Based learning, Dependent Variable participation learning.Result:The results showed there was a significant influenced beetwen pre n post of leraning participate.